New insights into a bacterial metabolic and detoxifying association responsible for the mineralization of the thiocarbamate herbicide molinate - Barreiros, Luisa (2010)
A novel pathway of molinate mineralization promoted by a defined mixed culture composed of five bacteria (named ON1 to ON5) was proposed previously. Evidence was obtained of a metabolic association between Gulosibacter molinativorax ON4T, capable of molinate breakdown, and the remaining bacteria. In the present study, the role of each isolate in that metabolic association was further explored and the possible synergistic effect of all the bacterial isolates for the stability of the mixed culture is discussed. The cleavage of the molinate thioester bond, whether occurring under aerobic or anaerobic conditions, releases ethanethiol (S-ethyl moiety) and an azepane moiety derivative, identified as azepane-1-carboxylic acid. This azepane moiety is degraded, in the presence of oxygen, by Pseudomonas strains ON1 and ON3 and G. molinativorax ON4T. Ethanethiol, which inhibits G. molinativorax ON4T, is consumed by Pseudomonas strain ON1 and Stenotrophomonas maltophilia ON2. Although a two-member mixed culture of G. molinativorax ON4T and Pseudomonas strain ON1 was able to promote the aerobic mineralization of molinate, after 20 successive transfers of the five-member mixed culture in mineral medium with molinate, none of these isolates were lost. The results obtained indicate that the whole mixed culture may have a higher fitness than the two-member culture, even when the basic degradative and cross-protection functions are assured.